Review on Dark Web and Its Impact on Internet Governance - Rajamanickam, Diviya Shini; Zolkipli, Mohamad Fadli (Journal of ICT in Education, 2021)
Cyber attackers use the Dark Web, a collection of facilities that are not visible to search engines and normal users, to explore a variety of illegal products and services. In this paper, the Dark Web and its impact on internet governance were analyzed. The findings of a review of the literature provide in-depth knowledge on the increasing number of crimes committed on the Dark Web, considering the economic, social, along ethical consequences of cybercrime on the Dark Web, as well as analyzing the consequences and methods for locating the criminals, as well as their drawbacks. Fraudsters, militants, and government-sponsored secret agents used the Dark Web where is among the most popular difficult together with unidentifiable channels to achieve their illicit goals. Crimes that were committed on the Dark Web are similar to criminal offenses committed in the real world. Nevertheless, the sheer size of the Dark Web, the unpredictability of the ecosystem, as well as the privacy and confidentiality afforded by Dark Web services, were also critical challenges in tracing criminals. Measuring the yachting Dark Web crime risks is a critical step in discovering alternative approaches to cybercrime. The study reveals that Dark Web services are available to arrest criminals, as well as digital facts and evidence, should be analyzed and applied in a way that allows Internet Governance.